Genetic and lifestyle risk factors for advanced liver disease among men and women. Issue 2 (28th July 2019) - Sahlman, Perttu; Nissinen, Markku; Puukka, Pauli; Jula, Antti; Salomaa, Veikko; Männistö, Satu; Lundqvist, Annamari; Valsta, Liisa; Perola, Markus; Färkkilä, Martti; Åberg, Fredrik
Abstract: Background and Aim: Liver disease is traditionally categorized as alcoholic and non‐alcoholic. We studied various risk factors predictive of advanced non‐viral liver disease in general population and analyzed the interaction between these factors and alcohol consumption. Methods: Persons without underlying liver disease who participated in the Health2000 or FINRISK studies 1992–2012 comprised a cohort of 41 260 individuals. Pattern of alcohol consumption and metabolic, lifestyle‐related, and anthropometric parameters were analyzed with Cox regression analysis using severe liver disease hospitalization, cancer, or death as end‐point. Viral liver diseases were excluded. Results: A total of 355 liver events occurred during the mean 12.4‐year follow‐up (511 789 person‐years). In the multivariate model, age (hazard ratio [HR] 1.03, P = 0.0083 for men; HR 1.04, P = 0.0198 for women), waist‐to‐hip ratio (WHR) (HR 1.52, P = 0.0006 for men; HR 1.58, P = 0.0167 for women), patatin‐like phospholipase‐containing domain 3 mutations (HR 1.9, P = 0.024 for men; HR 2.7, P = 0.0109 for women), and weekly binge drinking (HR 2.4, P = 0.0024 for men; HR 7.4, P < 0.0001 for women) predicted development of severe liver disease. Among men, diabetes (HR 2.7, P = 0.0002), average alcohol consumption (HR for 10 g/day 1.1, P = 0.0022), non‐married status (HR 1.9, P = 0.0397 for single; HR 2.4, P = 0.0002 for widowed/separated), and serum high‐density lipoprotein (HR 2.2, P = 0.0022) and non‐high‐density lipoprotein cholesterol (HR 1.2, P = 0.0237) were additional risk factors. Alcohol intake increased the risk especially among persons with high WHR ( P for interaction 0.009). Conclusions: Age, patatin‐like phospholipase‐containing domain 3 haplotype, and WHR increase the risk for development of severe liver disease. We found strong synergism between alcohol and central obesity. Binge drinking is an additional risk factor.